Water quality index based on fuzzy logic applied to the Aburra river basin in the jurisdiction of the Metropolitan Area. (2012)
The inherent uncertainties, subjectivity, and engineering challenges in environmental problems are increasingly being worked upon computing methods based on artifi cial intelligence (AI), including computerized tools that allow an analyst to use approximate reasoning with incomplete and inaccurate information and with the support of an expert in the fi eld. In order to evaluate the applicability of this tool, this paper presents the development of a new water quality index based on fuzzy logic called the “fuzzy water quality index” (FWQI). This index is compared to the NSF water quality index (NSFWQI) and with the water quality index (ARWQI) obtained for the project “Red Río Fase I” for the Medellin metropolitan area environmental authority. The new FWQI provided reasonable correlations and results in comparison to the other two reference indexes. Finally, the FWQI could be used as a decision maker in the water management of Aburra River.